PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEAKTIFAN BERTANYA DAN BERDISKUSI SISWA KELAS X MIA 3 SMA NEGERI 7 SURAKARTA TAHUN PELAJARAN 2014/2015 - Lilis Yuli Pramesti; Slamet Santosa; Suwarno Suwarno (Universitas Sebelas Maret, 2015)
The objective of research was to improve the questioning and discussion activeness through applying inquiry learning model in X MIA 3 graders of State Senior High School 7 Surakarta in the school year of 2014/2015. This study was a Classroom Action Research (CAR), each of which consisted of four stages: planning, acting, observing and reflecting. The data consisted of student questioning and discussion activeness collected through observation, interview and supporting data from documentation. The data validation was tested using triangulation technique. The data analysis was conducted using a descriptive qualitative technique. The research procedure employed spiral model. The result of research with improvement of questioning activeness was indicated by the improved contribution of students based on knowledge dimension in which 13 students posed factual questions, 19 students posed conceptual questions, and 16 students posed procedural questions in cycle I; 26 students posed factual questions, 21 students posed conceptual questions, 2 students posed metacognitive questions, and 11 students posed procedural questions in cycle II. In addition, it was also indicated by knowledge dimension based on thinking process dimension in which 18 students posed C1 questions, 23 students posed C2 questions, 9 students posed C4 questions, and 3 students posed C6 questions in cycle I. 16 students posed C1 questions, 24 students posed C2 questions, 4 students posed in C3 questions, 15 students posed C4 questions, 3 students posed C5 questions, and 10 students posed C6 questions in cycle II. The improvement of discussion activeness was indicated by the increased gain of mean percentage from 63.86% in cycle I and increased to 78.19% in cycle II.The conclusion of research was that the application of inquiry learning model could improve the questioning and discussion activeness through applying inquiry learning model in the 10th MIA 3 graders of SMA Negeri 7 Surakarta in the school year of 2014/2015. Keywords: Inquiry learning model, questioning activeness, discussion activeness